Method for modifying phenolic resin by asphalt microspheres, prepared modified phenolic resin and application
By using mesophase asphalt microspheres for surface modification, a stable chemical bonding and crosslinking structure with phenolic resin is formed, which solves the problems of low carbon residual rate and insufficient heat resistance in traditional phenolic resins at high temperatures, and achieves efficient modification of phenolic resins, significantly improving its performance and application range.
Patent Information
- Application Number
- CN202411916436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional phenolic resins have low carbon residual rate and insufficient heat resistance at high temperatures, which limits their application in the field of carbon/carbon composite materials. The existing modification methods are complex in processes and high in cost, making it difficult to achieve industrialization.
Mesophase asphalt microspheres are used as modifiers, and their compatibility and adhesion with phenolic resin are improved through surface modification treatment, forming a stable chemical bonding and cross-linking structure, and improving the carbon residual rate and heat resistance of phenolic resin.
It significantly improves the carbon residual rate, heat resistance and mechanical properties of phenolic resins, reduces the modification cost, and achieves a wider range of application fields, especially in the field of carbon/carbon composite materials.
Smart Images

Figure BDA0005206924300000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and more specifically, to a method for modifying phenolic resin with asphalt microspheres, the prepared modified phenolic resin and its application. Background Art
[0002] As an important thermosetting resin, phenolic resin is widely used in coatings, adhesives, molding compounds, friction materials and other fields due to its excellent mechanical properties, electrical insulation and corrosion resistance. However, traditional phenolic resin has disadvantages such as unsatisfactory residual carbon rate, high brittleness and insufficient heat resistance, which limits its large-scale application in high-end fields, especially in the field of carbon / carbon composite materials. Therefore, modifying phenolic resin to improve its residual carbon rate and other properties has always been a hot topic of research.
[0003] At present, the modification technology of phenolic resin mainly increases the rigid structure in the molecular chain of phenolic resin by chemical method to improve its performance, but this method is complicated and costly. It is necessary to provide a new modification method to improve the residual carbon rate of phenolic resin, and the modification method is simpler and easier to realize industrialization. Summary of the invention
[0004] In order to increase the residual carbon rate of phenolic resin and make the modification method simpler and easier to industrialize, the present application provides a method for modifying phenolic resin with asphalt microspheres, the prepared modified phenolic resin and its application.
[0005] In a first aspect, the present application provides a method for modifying a phenolic resin with asphalt microspheres, using the following technical solution: A method for modifying a phenolic resin with asphalt microspheres, comprising the following steps: S1. Material preparation: preparing phenolic resin and mesophase asphalt microspheres as raw materials; S2, pretreatment: performing surface modification treatment on the mesophase asphalt microspheres to obtain pretreated asphalt microspheres; S3, mixing the pretreated asphalt microspheres obtained in step S2 with phenolic resin, a curing agent and a catalyst, and then curing and molding the mixture to obtain a modified phenolic resin.
[0006] By adopting the above technical scheme, since the residual carbon rate of phenolic resin is low, it generates difficult-to-graphitize carbon after high-temperature carbonization, resulting in its weak heat resistance. Therefore, in this application, mesophase asphalt microspheres are used as a modifier to modify the phenolic resin. The mesophase asphalt has a high residual carbon rate and a high degree of graphitization after carbonization. What is more important is that the mesophase asphalt is mainly composed of polycyclic aromatic hydrocarbons, containing a large number of aromatic groups and double bond structures. Under the conditions of a catalyst and a curing agent, the mesophase asphalt can form a stable chemical bond with the phenolic resin. In this way, the phenolic resin itself will form a cross-linked structure in this process, and it can also react with the mesophase asphalt. A cross-linked structure is also formed between the asphalt microspheres, and ultimately a richer cross-linked structure is formed inside the system, so that the linear small molecules of the phenolic resin are cross-linked and solidified to form a three-dimensional network polymer structure, thereby increasing its residual carbon rate through its chemical modification. On the other hand, in this application, the mesophase asphalt is added in the form of microspheres, which greatly increases its specific surface area, thereby increasing its electrostatic adsorption-physical cross-linking effect on nearby molecules and extending the path of impact crack propagation. In this way, not only can the chemical action of the mesophase asphalt be used to increase its residual carbon rate, but also the toughness of the phenolic resin can be enhanced by adding it in the physical form of microspheres, thereby further improving its heat resistance.
[0007] Moreover, in the present application, the asphalt microspheres are first surface-modified and then mixed and cured with the phenolic resin, which can improve their compatibility and adhesion with the phenolic resin, and the surface treatment of the asphalt microspheres can ensure that the appropriate bonding force is formed between the asphalt microspheres and the phenolic resin to form an effective interface, which can significantly improve the carbon residue rate, heat resistance and mechanical properties of the phenolic resin, while not directly causing the brittle fracture of the resin matrix due to excessive bonding force, and has the comprehensive performance of high carbon residue rate and toughness, and improves its heat resistance. Moreover, the mesophase asphalt is a product separated from the asphalt mother liquor, which is low in price and significantly reduces the modification cost.
[0008] Optionally, the surface modification of mesophase pitch microspheres in step S2 specifically includes the following steps: S2-1, soaking the mesophase pitch microspheres in water, rinsing them repeatedly, and then drying them; S2-2, spraying the treatment liquid formed by mixing the silane coupling agent with water on the surface of the mesophase asphalt microspheres; S2-3, drying treatment to obtain pretreated mesophase pitch microspheres, and then proceed to step S3.
[0009] By adopting the above-mentioned technical scheme, although the phenolic resin and the intermediate phase asphalt both contain aromatic structures, which make them compatible to a certain extent, in the process of the intermediate phase asphalt forming asphalt microspheres, the polar groups and active groups on the surface of the asphalt microspheres will spontaneously flip inward to reduce the surface energy, thereby reducing the compatibility and adhesion between the asphalt microspheres and the phenolic resin to a certain extent. Therefore, in the present application, the intermediate phase asphalt microspheres are first treated with a silane coupling agent and then modified with a phenolic resin. The silane coupling agent can form chemical bonds with the functional groups on the surface of the asphalt microspheres, thereby making it easier to interact with the phenolic resin, thereby improving its adhesion and compatibility with the phenolic resin, and reducing the occurrence of peeling, thereby improving the residual carbon rate and toughness comprehensive performance of the intermediate phase asphalt modified phenolic resin.
[0010] Optionally, in step S2-1, the mesophase asphalt microspheres are immersed in water for 50-70 minutes.
[0011] By adopting the above technical scheme, when the surface of the intermediate phase asphalt microspheres is pretreated, the intermediate phase asphalt microspheres are first immersed in water. This not only removes surface impurities, but more importantly, water molecules can penetrate into the tiny pores on the surface of the intermediate phase asphalt microspheres, making the surface of the microspheres more moist. This is more conducive to the penetration and uniform distribution of the subsequent silane coupling agent treatment liquid, thereby improving its pretreatment effect. In addition, the silane coupling agent forms a certain dispersion state in the aqueous solution, making the surface of the asphalt microspheres more suitable for the binding of the silane coupling agent, thereby improving the pretreatment effect, and further helping to improve the adhesion and modified interface formation between the intermediate phase asphalt microspheres and the phenolic resin, thereby increasing its residual carbon rate.
[0012] Optionally, the mass percentage of the silane coupling agent in the treatment solution in step S2-2 is 5-20%.
[0013] By adopting the above technical solution, when the treatment liquid with the above ratio is selected, it has better flow permeability and has a better modification pretreatment effect on asphalt microspheres.
[0014] Optionally, alkylphenol polyoxyethylene ether and sodium dodecyl diphenyl oxide disulfonate are further added to the treatment liquid in step S2-2, the mass proportion of alkylphenol polyoxyethylene ether is 0.1-0.3%, and the mass proportion of sodium dodecyl diphenyl oxide disulfonate is 0.5-1.5%.
[0015] By adopting the above-mentioned technical scheme, it is precisely because the intermediate phase asphalt in this application is added in the form of microsphere particles that the asphalt microspheres and the phenolic resin are easily peeled off, affecting the formation of their interface. Therefore, on the one hand, the adhesion between the asphalt microspheres and the phenolic resin is improved by pretreatment with a silane coupling agent in this application. On the other hand, alkylphenol polyoxyethylene ether is also added when pretreating the asphalt particles in this application, which can reduce the interfacial tension between the asphalt particles and the phenolic resin and promote the mixing and close bonding of the two. Sodium dodecyl diphenyl ether disulfonate can form a negative charge layer on the surface of the asphalt microspheres, and electrostatically interact with the positively charged groups in the phenolic resin, thereby enhancing the adhesion between the two and reducing peeling, thereby improving the performance of the modified phenolic resin.
[0016] Optionally, in step S3, the added mass ratio of pretreated asphalt microspheres, phenolic resin, curing agent and catalyst is (1-5):100:(1-3):(0.05-0.1).
[0017] Optionally, the particle size of the mesophase asphalt microspheres is 5-10 μm.
[0018] By adopting the above technical solution, the intermediate phase asphalt microspheres are controlled to be within a suitable particle size range, which can not only form a uniform distribution in the phenolic resin matrix, but also provide more interface contact area, which helps to enhance the interaction between the asphalt microspheres and the phenolic resin, and can form a more compact stacking structure to improve its impact toughness.
[0019] Optionally, the curing agent is one or two of catechol, alum and ammonium chloride; The catalyst is an acidic catalyst or a basic catalyst. The acidic catalyst is specifically one or more of hydrochloric acid, phthalic acid and oxalic acid. The basic catalyst is specifically one or more of sodium hydroxide, potassium hydroxide and barium hydroxide.
[0020] By adopting the above-mentioned technical scheme, after the asphalt microspheres are mixed with the phenolic resin in the present application, under the action of the curing agent and the catalyst, a stable chemical bond is formed between the asphalt microspheres and the phenolic resin, and the linear small molecules of the phenolic resin can be cross-linked and cured into a three-dimensional network polymer structure, which helps to further increase the residual carbon rate of the modified phenolic resin and improve the heat resistance.
[0021] Optionally, the specific parameters of the curing molding in step S1 are: first treat at 75-85°C for 50-70min, then heat to 110-130°C for 1.5-2.5h, then heat to 150-170°C for 1-2h, and finally treat at 160-180°C for 1.5-2.5h.
[0022] Optionally, the specific parameters of the curing molding in step S1 are: first treat at 80°C for 60 minutes, then heat to 120°C for 2 hours, then heat to 160°C for 1.5 hours, and finally treat at 170°C for 2 hours.
[0023] By adopting the above technical scheme and controlling the above treatment temperature and treatment time, the active functional groups such as phenolic hydroxyl groups in the phenolic resin and the active functional groups such as methylene groups in the mesophase asphalt microspheres are promoted to form chemical crosslinks, thereby introducing aromatic groups into the phenolic resin and increasing its residual carbon rate. In addition, the introduction of unsaturated double bonds on the mesophase asphalt microspheres may also polymerize under heating conditions to increase their crosslinking density. It is found that the residual carbon rate of the modified phenolic resin is greatly improved after the above high-temperature curing.
[0024] During the curing process, internal stress will be generated due to the different shrinkage rates of phenolic resin and asphalt microspheres, resulting in cracks or peeling at the interface, which will reduce the performance of the modified phenolic resin. Therefore, in the present application, the high-temperature curing process is first treated at a lower temperature of 80°C to achieve preheating between the intermediate phase asphalt microspheres and the phenolic resin. This can reduce the difference in thermal shrinkage between the two during the curing process, and finally continue to maintain the curing temperature at high temperature for a period of time. On the one hand, the cross-linking curing reaction can be further completed, and on the other hand, the participating stress can be eliminated, thereby improving the performance of the final modified phenolic resin.
[0025] Optionally, the curing molding in step S3 is performed under molding conditions at 30-50 MPa.
[0026] By adopting the above technical solution, a certain pressure is applied to promote the cross-linking of the system on the one hand, and to prevent the existence of pores inside the phenolic resin due to the volatilization of small molecules during the curing process of the phenolic resin on the other hand.
[0027] Optionally, hexamethylenetetramine is further added in step S3, and the mass ratio of phenolic resin to hexamethylenetetramine is 100:(0.05-0.08).
[0028] By adopting the above technical scheme, hexamethylenetetramine is added as a cross-linking agent, which can undergo a cross-linking reaction with the phenolic resin to form a network of planar lamellar molecules, and then further cross-link with the condensed aromatic hydrocarbon molecules in the mesophase asphalt microspheres to generate a larger-sized mesophase molecular structure. This not only improves the compatibility of the phenolic resin and the mesophase asphalt microspheres, but also significantly improves its modification treatment. The final modified phenolic resin has a higher residual carbon rate and a certain toughness to prevent its brittle fracture.
[0029] Optionally, the specific operation of step S3 is: first, mix phenolic resin with polyethylene adipate, then add modified waste rubber powder and the pretreated asphalt microspheres in step S3, stir and mix, add curing agent and catalyst, and mix and cure to form, wherein the modified waste rubber powder is obtained by modification with a silane coupling agent.
[0030] Optionally, the mass ratio of polyethylene adipate to phenolic resin is (0.5-1.5):100, and the mass ratio of modified waste rubber powder to phenolic resin is (0.5-0.8):100.
[0031] By adopting the above technical scheme, the molecular structure and physical structure of polyethylene adipate as a modifier in the present application are similar to those of phenolic resin, and the polyethylene adipate has good compatibility with phenolic resin. The surface morphology of the waste rubber powder modified by the silane coupling agent is similar to that of the pretreated asphalt microspheres modified by the silane coupling agent. The addition of the waste rubber powder can achieve a toughening effect, and an interpenetrating network is formed between polyethylene adipate and the waste rubber powder and asphalt, thereby improving the compatibility and bonding strength. The phenolic resin finally obtained has better comprehensive properties, and the phenolic resin and the polyethylene adipate have good compatibility. The mixture of ethylene glycol adipate forms a continuous phase, while the modified waste rubber powder and pretreated asphalt microspheres serve as dispersed phases. By controlling the above raw materials and the amount of addition, the compatibility of the mixture is controlled to be comparable, which is neither completely compatible nor completely compatible, so that an island morphology structure is formed after the above raw materials are mixed. This helps to effectively disperse and absorb impact energy, reduce stress concentration and crack propagation inside the resin, and help to improve the impact toughness of the modified phenolic resin. In addition, the dispersion can support and protect the surrounding phenolic resin, reduce its pyrolysis rate, and increase the residual carbon rate.
[0032] In a second aspect, the present application provides a modified phenolic resin, which adopts the following technical solution: A modified phenolic resin is prepared by any one of the methods for modifying a phenolic resin with asphalt microspheres.
[0033] By adopting the above-mentioned technical scheme and modifying the phenolic resin by the method provided in this application, the carbon residue rate, impact toughness, heat resistance, flame retardancy, dimensional stability and other properties of the phenolic resin can be significantly improved. In addition, asphalt, as a low-cost material, is introduced in the form of microspheres to improve its toughness while reducing the modification cost of the phenolic resin.
[0034] In a second aspect, the present application provides an application of a modified phenolic resin, using the following technical solution: The invention discloses an application of a modified phenolic resin in a carbon / carbon composite material or carbon paper.
[0035] By adopting the above technical scheme, the modified phenolic resin in the present application has a higher residual carbon rate, impact toughness and heat resistance and has a wider application field. It can not only be applied to high-end coatings, high-performance adhesives, friction materials, etc., but also has broad application prospects in carbon / carbon composite material components for thermal fields of photovoltaic single crystal furnaces.
[0036] In summary, this application has the following beneficial effects: 1. In this application, mesophase asphalt microspheres are used as a modifier to modify the phenolic resin. Under the conditions of a catalyst and a curing agent, the mesophase asphalt can form a stable chemical bond with the phenolic resin, and the linear small molecules of the phenolic resin are cross-linked and cured to form a three-dimensional network polymer structure, thereby improving its residual carbon rate through its chemical modification. On the other hand, in this application, the mesophase asphalt is added in the form of microspheres, which greatly increases its specific surface area, thereby increasing its electrostatic adsorption-physical cross-linking effect on nearby molecules and extending the path of impact crack propagation. In this way, not only can the chemical action of the mesophase asphalt be used to increase its residual carbon rate, but also its addition in the physical form of microspheres can enhance the phenolic resin. The toughness of the resin is improved, thereby further improving its heat resistance; 2. In the present application, the asphalt microspheres are first surface-modified and then mixed with the phenolic resin for curing. This can improve its compatibility and adhesion with the phenolic resin on the one hand, and the surface treatment of the asphalt microspheres can ensure that an appropriate bonding force is formed between the asphalt microspheres and the phenolic resin to form an effective interface. This bonding force can significantly improve the carbon residue rate, heat resistance and mechanical properties of the phenolic resin, while not directly causing the brittle fracture of the resin matrix due to excessive bonding force. It has the comprehensive performance of high carbon residue rate and toughness, and improves its heat resistance; and the intermediate phase asphalt is a product separated from the asphalt mother liquor, which is low in price and significantly reduces the modification cost; 3. The modified phenolic resin in this application has a higher residual carbon rate, impact toughness and heat resistance and has a wider range of applications. It can not only be used in high-end coatings, high-performance adhesives, friction materials, etc., but also has broad application prospects in carbon / carbon composite material components for thermal fields of photovoltaic single crystal furnaces. DETAILED DESCRIPTION
[0037] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0038] The phenolic resin in the present application is a thermosetting phenolic resin, preferably a phenolic resin with low viscosity and high reactivity, such as ammonia, barium, magnesium and the like phenolic resin.
[0039] The phenolic resin in the following examples is a thermosetting phenolic resin, and more specifically, an aminophenolic resin with a brand number of LQ and a model number of 11 produced by Jining Sunbright Biotechnology Co., Ltd. is selected; The mesophase asphalt microspheres in this embodiment are asphalt microspheres with a particle size of 5-10μm, which can be obtained by spray-drying the mesophase asphalt to obtain the target particle size, or can be commercially purchased. In the following embodiments, the mesophase asphalt microspheres are specifically selected from commercially purchased mesophase carbon microspheres, also known as secondary carbon microspheres, which are the products obtained by separating the mesophase small spheres from the asphalt mother liquor by centrifugation or emulsification and washing. In the following embodiments, the mesophase carbon microspheres purchased from Asia Pacific Zhongtan (Shanxi) New Material Technology Co., Ltd. are specifically selected, and the particle size is 10μm.
[0040] Example 1 A method for modifying phenolic resin with asphalt microspheres comprises the following steps: S1. Material preparation: preparing phenolic resin and mesophase asphalt microspheres as raw materials; S2, pretreatment: The mesophase asphalt microspheres are subjected to surface modification treatment to obtain pretreated asphalt microspheres, which specifically includes the following steps: S2-1, soak the mesophase pitch microspheres in water for 60 minutes, rinse them repeatedly for 4 times, and then dry them at 60°C for 8 hours to ensure that they are dry and free of impurities; S2-2, spraying a treatment liquid formed by mixing silane coupling agent KH-550 with water on the surface of the mesophase asphalt microspheres, wherein the mass percentage of silane coupling agent KH-550 in the treatment liquid is 12%; S2-3, drying at 80°C for 3h to obtain pretreated mesophase asphalt microspheres, S3, mixing the pretreated asphalt microspheres obtained in step S2 with phenolic resin, a curing agent and a catalyst, performing compression molding and curing at a pressure of 40 MPa, and then cooling in a furnace to obtain a modified phenolic resin.
[0041] In step S3, the mass ratio of the pretreated asphalt microspheres, phenolic resin, curing agent and catalyst is 3:100:2:0.08, and the curing agent is catechol, and the catalyst is phthalic acid; The specific temperature parameters for curing molding are: first treat at 80°C for 60 minutes, then heat to 120°C for 2 hours, then heat to 160°C for 1.5 hours, and finally treat at 170°C for 2 hours.
[0042] Example 2 A method for modifying phenolic resin with asphalt microspheres comprises the following steps: S1. Material preparation: preparing phenolic resin and mesophase asphalt microspheres as raw materials; S2, pretreatment: The mesophase asphalt microspheres are subjected to surface modification treatment to obtain pretreated asphalt microspheres, which specifically includes the following steps: S2-1, soak the mesophase pitch microspheres in water for 50 minutes, rinse them repeatedly for 4 times, and then dry them at 55°C for 10 hours to ensure that they are dry and free of impurities; S2-2, spraying the treatment liquid formed by mixing silane coupling agent KH-550 with water on the surface of the mesophase asphalt microspheres, wherein the mass percentage of silane coupling agent KH-550 in the treatment liquid is 5%; S2-3, drying at 70°C for 5 hours to obtain pretreated mesophase asphalt microspheres, S3, mixing the pretreated asphalt microspheres obtained in step S2 with phenolic resin, a curing agent and a catalyst, performing compression molding and curing under a pressure of 30 MPa, and then cooling in a furnace to obtain a modified phenolic resin.
[0043] Wherein, in step S3, the added mass ratio of the pretreated asphalt microspheres, phenolic resin, curing agent and catalyst is 1:100:1:0.05, and the curing agent is phenolsulfonic acid (p-hydroxybenzenesulfonic acid), and the catalyst is hydrochloric acid; The specific temperature parameters for curing molding are: first treat at 75°C for 70 minutes, then heat to 110°C for 2.5 hours, then heat to 150°C for 1 hour, and finally treat at 160°C for 2.5 hours.
[0044] Example 3 A method for modifying phenolic resin with asphalt microspheres comprises the following steps: S1. Material preparation: preparing phenolic resin and mesophase asphalt microspheres as raw materials; S2, pretreatment: The mesophase asphalt microspheres are subjected to surface modification treatment to obtain pretreated asphalt microspheres, which specifically includes the following steps: S2-1, soak the mesophase pitch microspheres in water for 70 minutes, rinse them repeatedly for 5 times, and then dry them at 65°C for 5 hours to ensure that they are dry and free of impurities; S2-2, spraying the treatment liquid formed by mixing silane coupling agent KH-550 with water on the surface of the mesophase asphalt microspheres, wherein the mass percentage of silane coupling agent KH-550 in the treatment liquid is 20%; S2-3, drying at 85°C for 2h to obtain pretreated mesophase asphalt microspheres, S3, mixing the pretreated asphalt microspheres obtained in step S2 with phenolic resin, a curing agent and a catalyst, performing compression molding and curing under a pressure of 50 MPa, and then cooling in a furnace to obtain a modified phenolic resin.
[0045] Wherein, in step S3, the added mass ratio of the pretreated asphalt microspheres, phenolic resin, curing agent and catalyst is 5:100:3:0.1, and the curing agent is ammonium chloride, and the catalyst is sodium hydroxide; The specific temperature parameters for curing molding are: first treat at 85°C for 50 minutes, then heat to 130°C for 1.5 hours, then heat to 170°C for 1 hour, and finally treat at 180°C for 1.5 hours.
[0046] Example 4 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that in step S2-1, the phenolic resin is directly rinsed instead of being immersed in water.
[0047] Example 5 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that during the curing and molding in step S3, the temperature is raised to 160° C. and treated for 1.5 hours before being directly cooled.
[0048] Example 6 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that during the curing and molding in step S3, the temperature is directly raised to 120° C. and treated for 2 hours.
[0049] Example 7 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that alkylphenol polyoxyethylene ether TX-10 and sodium dodecyl diphenyl oxide disulfonate are also added to the treatment liquid in step S2-2, the mass proportion of alkylphenol polyoxyethylene ether TX-10 is 0.2%, and the mass proportion of sodium dodecyl diphenyl oxide disulfonate is 1%.
[0050] Example 8 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that alkylphenol polyoxyethylene ether TX-10 and sodium dodecyl diphenyl oxide disulfonate are also added to the treatment liquid in step S2-2, the mass proportion of alkylphenol polyoxyethylene ether TX-10 is 0.1%, and the mass proportion of sodium dodecyl diphenyl oxide disulfonate is 0.5%.
[0051] Example 9 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that alkylphenol polyoxyethylene ether TX-10 and sodium dodecyl diphenyl oxide disulfonate are also added to the treatment liquid in step S2-2, the mass proportion of alkylphenol polyoxyethylene ether TX-10 is 0.3%, and the mass proportion of sodium dodecyl diphenyl oxide disulfonate is 1.5%.
[0052] Example 10 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that hexamethylenetetramine is further added in step S3, and the mass ratio of phenolic resin to hexamethylenetetramine is 100:0.05.
[0053] Embodiment 11 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that hexamethylenetetramine is also added in step S3, and the mass ratio of phenolic resin to hexamethylenetetramine is 100:0.08.
[0054] Example 12 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that polyethylene adipate and modified waste rubber powder are further added in step S3, and the specific operation of step S3 is: firstly, the phenolic resin and polyethylene adipate are mixed, and then the modified waste rubber powder and the pretreated asphalt microspheres in step S3 are added, and after stirring and mixing, a curing agent and a catalyst are added, and after mixing, curing and molding are performed, and the added mass ratio of polyethylene adipate to the phenolic resin is 1:100, and the added mass ratio of the modified waste rubber powder to the phenolic resin is 0.6:100; The modified waste rubber powder is prepared by the following method: The waste rubber powder was washed and dried, and then added into a silane coupling agent KH-550 solution prepared by silane coupling agent KH-550 and water with a mass concentration of 15%, stirred and soaked for 35 minutes, filtered, and then first dried at 65°C, and then treated at 150°C for 1 hour for consolidation.
[0055] Embodiment 13 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that polyethylene adipate and modified waste rubber powder are further added in step S3, and the specific operation of step S3 is: firstly, the phenolic resin and polyethylene adipate are mixed, and then the modified waste rubber powder and the pretreated asphalt microspheres in step S3 are added, and after stirring and mixing, a curing agent and a catalyst are added, and after mixing, curing and molding are performed, and the added mass ratio of polyethylene adipate to the phenolic resin is 0.5:100, and the added mass ratio of the modified waste rubber powder to the phenolic resin is 0.5:100; The modified waste rubber powder is prepared by the following method: The waste rubber powder was washed and dried, and then added into a silane coupling agent KH-550 solution prepared by silane coupling agent KH-550 and water with a mass concentration of 10%, stirred and soaked for 30 minutes, filtered, and then first dried at 60°C, and then solidified at 140°C for 70 minutes.
[0056] Embodiment 14 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that polyethylene adipate and modified waste rubber powder are further added in step S3, and the specific operation of step S3 is: firstly, the phenolic resin and polyethylene adipate are mixed, and then the modified waste rubber powder and the pretreated asphalt microspheres in step S3 are added, and after stirring and mixing, a curing agent and a catalyst are added, and after mixing, curing and molding are performed, and the added mass ratio of polyethylene adipate to the phenolic resin is 1.5:100, and the added mass ratio of the modified waste rubber powder to the phenolic resin is 0.8:100; The modified waste rubber powder is prepared by the following method: The waste rubber powder is washed and dried, and then added into a silane coupling agent KH-550 solution prepared by silane coupling agent KH-550 and water with a mass concentration of 20%, stirred and soaked for 40 minutes, filtered, and then first dried at 70°C, and then solidified at 160°C for 50 minutes.
[0057] Embodiment 15 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 12, except that an equal amount of modified scrap rubber powder is replaced by scrap rubber powder.
[0058] Example 16 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 12, except that no modified waste rubber powder is added in step S3.
[0059] Comparative Example 1 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that the mesophase asphalt microspheres are not treated in step S2.
[0060] Comparative Example 2 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that no curing agent and catalyst are added in step S3, and the phenolic resin is directly mixed with the pretreated asphalt microspheres and then cured and molded.
[0061] Comparative Example 3 A method for modifying phenolic resin with asphalt microspheres is carried out according to the method in Example 1, except that the mesophase asphalt microspheres in steps S1 and S2 are replaced with mesophase asphalt in equal amounts, and step S2 is not performed.
[0062] Performance Testing The modified phenolic resins prepared in the examples of the present application and the comparative examples were respectively tested for residual carbon rate (900°C) and elongation at break. The elongation at break test was specifically prepared by preparing the modified phenolic resins prepared in the examples of the present application and the comparative examples into 15 cm×3 cm×3 cm samples, and then testing the elongation at break. The test results are shown in Table 1 below: Table 1: Referring to the test results in Table 1 above, the modified phenolic resin prepared by the method in the embodiment of the present application has a higher residual carbon rate, and at the same time has a higher elongation at break and better toughness, which has broad application prospects in the fields of carbon-based materials such as carbon / carbon composite materials components or carbon paper for single crystal furnace thermal fields.
[0063] Referring to the test results of Example 1 and Example 4, when the mesophase asphalt microspheres in Example 4 were pretreated but not immersed in water, the performance of the modified phenolic resin was reduced, affecting the pretreatment effect and thus the final effect. Combined with the test results of Example 5 and Example 6, in Example 5, no subsequent insulation operation was performed after curing and molding, and the residual stress in the modified phenolic resin affected the toughness of the final modified phenolic resin. Combined with the test results in Example 6, when the phenolic resin and the mesophase asphalt microspheres were not preheated, the difference in thermal shrinkage between the two affected the final carbon residue rate and impact toughness of the phenolic resin.
[0064] Combined with the test results of Example 1 and Examples 7-9, when alkylphenol polyoxyethylene ether TX-10 and sodium dodecyl diphenyl ether disulfonate are added during the pretreatment of the mesophase asphalt microspheres, the residual carbon rate of the final modified phenolic resin is further significantly improved, and its impact toughness is also improved. Combined with the test results of Examples 10-11, the addition of hexamethylenetetramine helps to increase the crosslinking density of the modified phenolic resin, thereby increasing its residual carbon rate. Referring to the test results of Examples 12-14, when polyethylene adipate and silane coupling agent are added to the modified phenolic resin, it can not only significantly improve the residual carbon rate of the modified phenolic resin, but also significantly improve its impact toughness. Combined with the test results of Examples 15 and 16, when no modified waste rubber powder is added or the waste rubber powder is directly added without modification, its impact toughness is significantly reduced, and its residual carbon rate is also reduced.
[0065] Referring to the test results in Example 1 and Comparative Example 1, when the mesophase asphalt microspheres in Comparative Example 1 are directly added without pretreatment in step S2, the compatibility and adhesion between the mesophase asphalt microspheres and the phenolic resin are affected, and the residual carbon rate and impact toughness are significantly reduced. Combined with the test results of Comparative Example 2, when the phenolic resin and asphalt microspheres in Comparative Example 2 are directly cured and formed without adding a curing agent and a catalyst, the crosslinking between the phenolic resin and the pretreated asphalt microspheres is affected, and its performance is significantly reduced. Combined with the test results of Comparative Example 3, when the modified phenolic resin is directly added through the mesophase asphalt without adding it in the form of microspheres, although its residual carbon rate is high, its impact toughness is significantly reduced.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for modifying phenolic resin with asphalt microspheres, characterized in that: The following steps are involved: S1. Material preparation: preparing phenolic resin and mesophase asphalt microspheres as raw materials; S2, pretreatment: performing surface modification treatment on the mesophase asphalt microspheres to obtain pretreated asphalt microspheres; S3, mixing the pretreated asphalt microspheres obtained in step S2 with phenolic resin, a curing agent and a catalyst, and then curing and molding the mixture to obtain a modified phenolic resin.
2. The method for modifying phenolic resin with asphalt microspheres according to claim 1, characterized in that: The surface modification of mesophase pitch microspheres in step S2 specifically includes the following steps: S2-1, soaking the mesophase pitch microspheres in water, rinsing them repeatedly, and then drying them; S2-2, spraying the treatment liquid formed by mixing the silane coupling agent with water on the surface of the mesophase asphalt microspheres; S2-3, drying treatment to obtain pretreated mesophase pitch microspheres, and then proceed to step S3.
3. The method for modifying phenolic resin with asphalt microspheres according to claim 2, characterized in that: In step S2-1, the mesophase asphalt microspheres are immersed in water for 50-70 minutes.
4. The method for modifying phenolic resin with asphalt microspheres according to claim 2, characterized in that: The mass percentage of the silane coupling agent in the treatment solution in step S2-2 is 5-20%.
5. The method for modifying phenolic resin with asphalt microspheres according to claim 2, characterized in that: In step S2-2, alkylphenol polyoxyethylene ether and sodium dodecyl diphenyl oxide disulfonate are also added to the treatment liquid, the mass proportion of alkylphenol polyoxyethylene ether is 0.1-0.3%, and the mass proportion of sodium dodecyl diphenyl oxide disulfonate is 0.5-1.5%.
6. The method for modifying phenolic resin with asphalt microspheres according to claim 1, characterized in that: In step S3, the added mass ratio of pretreated asphalt microspheres, phenolic resin, curing agent and catalyst is (1-5):100:(1-3):(0.05-0.1).
7. The method for modifying phenolic resin with asphalt microspheres according to claim 1, characterized in that: The curing agent is selected from one or two of catechol, alum and ammonium chloride; The catalyst is an acidic catalyst or a basic catalyst.
8. The method for modifying phenolic resin with asphalt microspheres according to claim 1, characterized in that: The specific parameters of the curing molding in step S1 are: first, treat at 75-85°C for 50-70min, then heat to 110-130°C for 1.5-2.5h, then heat to 150-170°C for 1-2h, and finally treat at 160-180°C for 1.5-2.5h.
9. A modified phenolic resin, characterized in that: The method is as claimed in any one of claims 1 to 8 to modify the phenolic resin by using asphalt microspheres.
10. Use of the modified phenolic resin as claimed in claim 9 in carbon / carbon composite materials or carbon paper.
Citation Information
Patent Citations
Mesophase pitch modified ablation-resistant resin matrix material, preparation method and application thereof
CN113845746A